Pengaruh Ukuran Pemerintah Dan Pendapatan Asli Daerah (PAD) Terhadap Kinerja Keuangan Pada Pemerintah Kota Surabaya - Anissak Fitri Ramahdani; Sri Trisnaningsih (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The purpose of this research is to look into and assess the impact of local revenue and government size on the Surabaya municipal government's financial performance. This research uses quantitative research methods. In this study, the object of research used is the size of the Surabaya city government in this case, namely total assets and the annual report of Regional Original Revenue (PAD). The sample method applied in this research is purposive sampling method. The analytical method used is the multiple regression analysis and classical assumption test because this analysis is able to measure the strength of two or more variables with the help of the SPSS program. The results based on the results of the t test partially show a significance value of 0.013 < 0.05 and t count < t table, therefore partially the size of the Regional Government (UPD) has no effect on the Financial Performance of the Regional Government, while based on the results of the t test partially The significance value shows the results of 0.06 <0.05 and t count > t table, therefore Regional Original Income (PAD) has an effect on Regional Government Financial Performance. Keywords : Government Size, Regional Original Revenue, and Regional Government Financial Performance